From Passenger to Pilot – Using Formative Assessment to Support Students With Intellectual Disabilities to Become Self-Regulated Learners - Andersson, Catarina; Granberg, Carina (Frontiers in Education, 2022)
Students with intellectual disabilities (ID) risk leaving school without having the opportunity to develop their independence to become less reliant on others. This study aims to gain insights into how formative assessment as a teaching design can support self-regulated learning (SRL) among students with ID. Two experienced Swedish special school teachers, using formative assessment to support students’ SRL competence, participated in this study. Data consisted of the teachers’ written teaching descriptions, classroom observations, and teacher interviews. The analysis showed that the teachers managed to implement a formative classroom practice aiming to support the students to develop subject-matter knowledge as well as SRL skills. Three themes of challenges were identified: Low expectations and caretaking, Experiences of shortcomings, and Learning difficulties. Overcoming such challenges is discussed. The study shows promising examples of the use of theories and principles of formative assessment to promote SRL competence among students with ID, and also incentives for doing so.